Portuguese cultural standards from an Austrian perspective - Robalo, A.; Kainzbauer, A.; Durão, I. (Global Economics and Management Review (GEMREV), 2015)
The goal of this paper is to identify Portuguese cultural standards from the perspective of Austrian culture. The Cultural Standards Method is based on interviews with members of one culture who have extended working experience in a different culture. This method, based on a qualitative research approach, seeks to identify cultural differences on a subtler level than more traditional methods, such as cultural dimensions. The Portuguese cultural standards identified through interviews with 20 Austrians are as follows: fluid time management, relaxed attitude towards professional performance, importance of social relationships, bureaucracy and slow decision-making processes, indirect communication style, and flexible planning and organisational skills.